(untitled) (Studia Prawnicze / The Legal Studies, 2007)
W Polsce pierwsze unormowania dotyczące GMO wprowadzone zostały w 1997 r., co związane było z realizacją przewidzianego w Układzie o stowarzyszeniu między Polską a Wspólnotami Europejskimi obowiązku dostosowania prawa polskiego do prawa wspólnotowego. W 2001 r. przyjęta natomiast została pierwsza ustawa kompleksowo normująca problematykę związaną z GMO. Obecnie jednak prowadzone są prace nad nową ustawą, która zastąpić ma ustawę dotychczas obowiązującą. Projekt nowej ustawy - Prawo o organizmach gene tycznie zmodyfikowanych Rada Ministrów przyjęła 13 lutego 2007 r. Zakłada on, że ogólny zakaz uprawy roślin genetycznie zmodyfikowanych (GM) powinien być w Polsce utrzymany. Zakaz taki wprowadzono w maju 2006 r., dokonując nowelizacji ustawy o ochronie roślin i ustawy o nasiennictwie. Od ogólnego zakazu przewiduje się jednak w projektowanej ustawie wyjątek w postaci możliwości tworzenia specjalnych „stref wskazanych do prowadzenia upraw roślin GM” (strefy takie mogłyby być tworzone na mocy decyzji, które wydawałby minister do spraw rolnictwa w porozumieniu z ministrem do spraw środowiska i po zasięgnięciu opinii właściwej rady gminy). W świetle projektowanych rozwiązań regulacja GMO będzie w naszym kraju przedmiotem ożywionej debaty. Interesującego wkładu do tej dyskusji dostarczyć może analiza rozwiązań, jakie w odniesieniu do GMO przyjmowane sąw innych systemach prawnych. Niniejsze opracowanie poświęcone jest rozwiązaniom przyjętym przez Stany Zjednoczone Ameryki. Zostaną one poddane szczegółowej analizie i następnie porównane z podejściem do regulacji przyjmowanym przez Kanadę, Argentynę (krótko zarysowane zostanie również podejście Brazylii) oraz Wspólnotę Europejską. What constitutes an appropriate approach towards GMO regulation continues to be a subject of much controversy. This paper analyses the approach adopted by the United States, the global leader in the field of GMO development, commercialization, production and export. Under the 1986 US Coordinated Framework the primary responsibility to regulate biotechnology products, which includes GMO, is shared by three different federal regulatory agencies (USDA-APHIS, EPA and FDA). Each of them derives its authority from different federal statutes and focuses on different product categories. GMO have not been singled out as a separate category of products for purpose of their regulation, but fitted into existing product categories, depending on their traits and intended uses. Each of the three regulatory pathways needs therefore to be examined in detail. Further, to place the approach adopted by the US in a broader context the paper discusses the approaches adopted in several other jurisdictions, namely Canada and Argentina as well as the European Community, and seeks to compare them with the American regulatory approach. The United States, Canada and Argentina, all three being major global producers and exporters of GMO, share certain regulatory goals, concepts and principles. They base their regulatory frameworks on a premise that modem biotechnology used as a production method is not inherently risky. The similarities as well as the Solutions specific to each of these countries are discussed in the paper. Finally, the American approach towards GMO regulation is contrasted with the approach of the European Community. The two approaches differ significantly and the clash between them has become evident in the intemational arena, most clearly within the recent WTO dispute (between the US, Canada and Argentina being on one side of the dispute and the EC- on the other). Analysis and comparison of these regulatory systems may appear to be a valuable input into the discussion on how to regulate GMO, currently taking place in many countries, also in Poland - in particular in context of the current legislative steps taken to adopt a new Polish act on GMO.